2017
DOI: 10.3906/sag-1512-115
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of quality of life and cost-effectiveness of definitive surgery and the levonorgestrel intrauterine system as treatment options for heavy menstrual bleeding

Abstract: A total of 104 patients aged 20-55 years, with complaints of regular HMB, were enrolled in the study from January 2013 to June 2015. Ninety-eight women completed the study. The inclusion criteria were the presence of HMB, reproductive age, a completed family, failure of appropriate first-line oral medical therapy, normal Pap smear, no pelvic pathology on ultrasound, normal endometrial biopsy, and pictorial blood loss assessment chart scores of ≥100 (average of two consecutive cycles). The exclusion criteria we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…The mean duration of follow-up ranged from 49 to 57 months. A further 25 studies (including 1268 patients) met inclusion criteria for our additional population analogue, and described hysterectomy as a treatment of benign disease, specifically treatment of HMB/DUB [ 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 ]. Fifteen studies reported on 9 randomised controlled trials (RCTs), and 8 studies reported on separate cohort studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The mean duration of follow-up ranged from 49 to 57 months. A further 25 studies (including 1268 patients) met inclusion criteria for our additional population analogue, and described hysterectomy as a treatment of benign disease, specifically treatment of HMB/DUB [ 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 ]. Fifteen studies reported on 9 randomised controlled trials (RCTs), and 8 studies reported on separate cohort studies.…”
Section: Resultsmentioning
confidence: 99%
“…Using the NOS, 2/2 cohort studies into RRH [ 31 , 34 ] revealed moderate risk of bias, due to the small sample in the assessed cohort versus the baseline population, and lack of baseline assessments. Eight cohort studies [ 69 , 72 , 73 , 74 , 82 , 83 , 84 , 87 ] into treatment of HMB/DUB were assessed with NOS; 7/8 studies revealed moderate risk of bias, in the lack of baseline assessments and assessments of outcome ( Table S4 ). The Jadad scale for randomised controlled trials demonstrated moderate risk of bias in 6/9 trials [ 63 , 68 , 70 , 75 , 77 , 80 , 81 , 85 , 86 ], predominantly due to lack of clarity on blinding ( Table S3 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[11][12][13][14] A observational study conducted by Tariq N to find out clinical response, side effects, and patients acceptability of levonorgestrel -releasing intrauterine system (LNG-IUS). 15,16 Adult women were enrolled, where two groups were enrolled where 57 women with abnormal uterine bleeding and 16 married woman for contraception.…”
Section: Discussionmentioning
confidence: 99%
“…Decreased hemoglobin concentration by 0.36 to 0.94 g/dL in one year period has been found in copper IUD users (53) Non-steroidal antiinflammatory drugs (NSAIDs) are recommended to alleviate menstrual blood and cramping pain. Hormonal IUDs reduce menstrual bleeding day and menstrual blood loss with LNG which suppresses endometrium that is sensitive to enlargement by ovarian estrogen (54,55).…”
Section: Pelvic Inflammatory Disease (Pid)mentioning
confidence: 99%